Pengembangan Aplikasi Tracer Study Universitas Jabal Ghafur Menggunakan Framework Laravel - Sayed Achmady; Khairul Rizki; Cut Lilis Setiawati (Yayasan Sagita Akademia Maju, 2023)
Tracer study is a research center regarding alumni in terms of finding work, work situations, and the use of acquiring competence while at Jabal Ghafur University. Tracer studies can help overcome the problem of inequality in employment opportunities and efforts to improve it. For universities, information about competencies that are relevant to the world of work can help efforts to improve curriculum and learning systems. However, the availability of study data is incomplete and difficult to obtain. Some of what has been done is using social media, e-mail and by distributing cover letters in the form of questionnaires to alumni manually. For this reason, it is necessary to develop a tracer study application with a website using the Laravel Framework which has the advantage of using MVC (model view controller) using a software approach that separates application logic and presentation so that the time spent in developing this application becomes faster. The results from users of this application can help Jabal Ghafur University alumni search for the best graduates and alumni who plan to find work